A meta‐analysis of global avian survival across species and latitude. (22nd July 2020) - Scholer, Micah N.; Strimas‐Mackey, Matthew; Jankowski, Jill E.
Abstract: Tropical birds are purported to be longer lived than their temperate counterparts, but it has not been shown whether avian survival rates covary with latitude worldwide. Here, we perform a global‐scale meta‐analysis of 949 estimates from 204 studies of avian survival and demonstrate that a latitudinal survival gradient exists in the northern hemisphere, is dampened or absent for southern hemisphere species, and that differences between passerines and nonpasserines largely drive these trends. We also show that while extrinsic factors related to climate were poor predictors of apparent survival compared to latitude alone, the relationship between apparent survival and latitude is strongly mediated by intrinsic traits – large‐bodied species and species with smaller clutch size had the highest apparent survival. Our findings reveal that differences among intrinsic traits and whether species were passerines or nonpasserines surpass latitude and its underlying climatic factors in explaining global patterns of apparent avian survival. Abstract : We synthesize data on avian survival rates from around the world to examine the hypothesis of latitudinal gradient in survival and explore whether these patterns can be explained using a combination of environmental climate factors and species intrinsic traits. We find evidence of a negative relationship between survival and latitude, but only in northern hemisphere passerines and birds from South America. These patterns are best accounted for by a considering a combination of species body mass and clutch size.